CLINICAL AND LABORATORY FEATURES OF THE COURSE OF PANCREATIC CANCER - Umarova T. A.; Kudratova Z. E.; Normurodova F. (Web of Journals Publishing, 2025)
The term “pancreatic cancer” includes a group of malignant neoplasms that develop in the pancreatic parenchyma: head, body and tail of the pancreas. The main clinical manifestations of these diseases are abdominal pain, anorexia, weight loss, general weakness, jaundice [7,8].
Keywords: Pancreatic cancer, clinical manifestations, malignant tumor, regional lymph nodes, old age.